Effects of microplastics alone and with adsorbed benzo(a)pyrene on the gills proteome of Scrobicularia plana - Bebianno, Maria (2022)
Microplastics (MPs) are globally present in the marine environment, but the biological effects on marine organisms at the molecular and cellular levels remain scarce. Due to their lipophilic nature, MPs can adsorb other contaminants present in the marine environment, which may increase their detrimental effects once ingested by organisms. This study investigates the effects of low-density polyethylene (PE) MPs with and without adsorbed benzo[a]pyrene in the gills proteome of the peppery furrow shell clam, Scrobicularia. plana. Clams were exposed to PE MPs (11-13 µm; 1 mg L-1) for 14 days. BaP was analyzed in whole clams’ soft tissues, and a proteomic approach was changes, oxidative stress fatty acid, DNA binding and, neurotransmission highlighting the potential risk of this type of MPs for the clam health. Conversely, when clam gills were exposed to MPs adsorbed with BaP a higher differentiation of protein expression was observed that besides changes in cytoskeleton and cell structure, oxidative stress, energy metabolism and DNA binding also induce changes in glucose metabolism, RNA binding and apoptosis. These results indicate that the presence of both stressors (MPs and BaP) havea higher toxicological risk to the health of S. plana.